2D/2D Transition‐Metal‐Sulfide Self‐Assembly Enables a Huge Tolerance to High Concentration Cr(VI) and a Prominent Photocatalytic Reduction Performance. Issue 3 (11th January 2023) - Zhang, Qian; Shao, Jingze; Geng, Zhibin; Liu, Chang; Li, Liping; Li, Guangshe
Abstract: Two‐dimensional (2D) transition‐metal‐sulfides always suffer from poor optical absorption ability, serious photogenerated carrier recombination, and lack of tolerance to high concentration Cr(VI), which limit their wide applications. Herein, 2D MoS2 nanosheets are in situ grown on 2D 5 % Cu‐doped ZnIn2 S4 nanosheets to fabricate self‐assembly via a two‐step solvothermal method. The incorporation of Cu broadens the optical response range of self‐assembly and introduces an acceptor trap level that changes the valence band allocation of ZnIn2 S4 nanocrystals, which improves the separation and migration of photogenerated electron‐hole pairs. As a result, complete photoreduction of Cr(VI) is surprisingly achieved for 2D/2D self‐assembly MoS2 /Cu−ZnIn2 S4 in 4 min under visible light irradiation (λ≥400 nm) without sacrificing any agents. Moreover, this self‐assembly is further indicated to have a strikingly huge tolerance to high concentration Cr(VI) (250 mg ⋅ L −1 ), and the photoreduction activity of Cr(VI) is almost not disturbed by high concentration inorganic ions in wastewater. All these merits demonstrate that 2D/2D transition‐metal‐sulfide self‐assembly may find many practical applications in water cleaning and environmental remediation. Abstract : 2D/2D Transition‐Metal‐Sulfide for Photocatalytic Applications : A self‐assembly ultra‐thin 2D/2D MoS2 /Cu−ZnIn2 S4 with a compact interface creates a stage for the rapid transfer of photogenerated electrons between 2D components and shows an excellent photocatalytic Cr(VI) reduction performance.